DAMPAK PENGESAHAN RUU OMNIBUS LAW DALAM PERSPEKTIF HUKUM KETENAGAKERJAAN - Habibah Zulaiha (Fakultas Syariah IAIN Kediri, 2022)
In his first speech after being sworn in as President of Indonesia 2019-2024, on Sunday, October 20, 2019, President Joko Widodo alluded to making a concept of legislation called Omnibus Law. According to Jokowi, through omnibus law, there will be a simplification of regulatory constraints that are currently convoluted and long. It is a law that simultaneously revises several laws. To realize this, Jokowi will invite the House of Representatives to discuss 3 (three) major laws, including the Law (UU) on Taxation, Job Creation and the Law on the Empowerment of Small and Micro Medium Enterprises (MSMEs). Each of these laws will become omnibus law. There are two points of interest in the issue of the Establishment of the Omnibus Law Bill namely the Work Copyright Bill and the Tax Bill. The purpose of the establishment of the Omnibus Law Bill according to the President of the Republic of Indonesia, Joko Widodo, is for simplifying the regulatory constraints that are often convoluted and takes long time. The next, omnibus laws are also expected to strengthen the national economy by improving the investment ecosystem. It also to improve Indonesia's competitiveness to encounter the uncertainty situation and deceleration of global economy. The research method applied in this study was empirical research. This method was done through consideration of research specialization including descriptive analysis. It describes the discussions of studies to get certainty of legal position related to the impact of the ratification of the omnibus law bill on job creation between the company and its employees, connected with the laws and practices of civil and employment law. The government has issued a policy by providing legal position and certainty for employment through labour law 79 law and 1,244 articles affected by omnibus law copyright employment, with details: simplification of licensing in 52 laws with 770 articles, investment requirements in 13 laws with 24 articles; employment in 3 laws with 55 articles, ease, empowerment, and protection of UMK-M in 3 laws with 6 articles and ease of effort in 9 laws with 23 articles. Furthermore, there is a research and innovation support section in 2 laws with 2 articles, government administration in 2 laws with 14 articles, the imposition of sanctions in 49 laws with 295 articles, land procurement in 2 laws with 11 articles, investment and government projects in 2 laws with 3 articles, and economic areas in 5 laws with 38 articles. Some things are important in the position and legal certainty contained in the articles of this law. There are some suggestions for the employees and employer. The first, for employment, the existing laws and regulations should be read in advance the content of the legislation as to what. The second, employees should have good understanding at legislation that is in accordance with procedures or even the policies of leaders who are the opposite. If it can be understood correctly so that there is no misperception that can harm employment / employees because of errors in making a policy decision.